Answer:
The answers are:
1. 2(x2 + 6x + 9) = 3 + 18
2. 2(x2 + 6x) = 3
Let's take a look at the first choice:
2(x² + 6x + 9) = 3 + 18
Now, we will multiply 2 with every member of the other multiplier on the left side:
2·x² + 2·6x + 2·9 = 3 + 18
2x² + 12x + 18 = 3 + 18
2x² + 12x - 3 = 18 - 18
2x² + 12x - 3 = 0
Let's take a look at the second choice:
2(x² + 6x) = 3
Now, we will multiply 2 with every member of the other multiplier on the left side:
2·x² + 2·6x = 3
2x² + 12x = 3
2x² + 12x - 3 = 0 Man that was so hard MARK ME Brainilest Thanks Peace
Explanation: